2007
DOI: 10.1136/aim.25.3.72
|View full text |Cite
|
Sign up to set email alerts
|

Are Auricular Maps Reliable for Chronic Musculoskeletal Pain Disorders?: A Double-Blind Evaluation

Abstract: Aim To examine the proposed somatotopic relation between the regions in which patients report musculoskeletal pain and tender points located on the external ears according to a map based on commonly used auricular acupuncture maps. Methods Twenty-five patients (16 women) from a chronic pain clinic were included. Patients were asked, before examination of the external ears, if they had past or present musculoskeletal pain in any of 11 body regions. An ear map, collapsed into 11 zones representing the musculoske… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 13 publications
(14 reference statements)
0
14
0
1
Order By: Relevance
“…9 Although we understand the different phases described in the literature, the reference of auricular map used in this study was used in previous publications for either persistent or chronic musculoskeletal pain. 10,11 (4) The somatotopic organization of external auricles: Although auricular acupuncture maps have been used for several decades as guides for diagnosis and treatment, scientists have not yet been able to demonstrate or validate such a highly specific functional map of the external auricles. 10,14 A clinical study 10 indicated the lack of agreement between the region of patients' reported musculoskeletal pain and location of the tender zones of the external ears as assessed by a pressure stylus with an auricular acupuncture map used in the landmark auricular acupuncture research article.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…9 Although we understand the different phases described in the literature, the reference of auricular map used in this study was used in previous publications for either persistent or chronic musculoskeletal pain. 10,11 (4) The somatotopic organization of external auricles: Although auricular acupuncture maps have been used for several decades as guides for diagnosis and treatment, scientists have not yet been able to demonstrate or validate such a highly specific functional map of the external auricles. 10,14 A clinical study 10 indicated the lack of agreement between the region of patients' reported musculoskeletal pain and location of the tender zones of the external ears as assessed by a pressure stylus with an auricular acupuncture map used in the landmark auricular acupuncture research article.…”
Section: Discussionmentioning
confidence: 99%
“…In order to maintain consistency with studies published in the literature, the study protocol was based on two previous studies. 10,11 All of the participants were asked to fill out an anonymous self-report inventory, which allowed them to report whether they experienced any musculoskeletal pain and to specify its location and duration. Once a participant filled out the inventory sheet, he/she was escorted to an isolated room with a comfortable recliner.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both tenderness and low electrical resistance were signifi cantly more present at corresponding points. 5 In a subsequent study Andersson and colleagues 6 could not replicate Oleson's positive results, but their study was limited by small sample size, failure to examine the posterior surface of the ear and arbitrary, non-standard classifi cation of zones.…”
Section: Introductionmentioning
confidence: 94%